COVID-19 Induced Fulminant Myocarditis – A Case Study - Mohamed Eltaieb Ali; Ashraf Alakkad (New Horizons in Medicine and Medical Research Vol. 11, 2022)
A 31-year-old patient initially presented to another clinic with symptoms of moderate fever, throat pain, and widespread myalgia. The patient’s COVID-19 test showed positive, indicating that he had the virus. Because the patient’s chest CT scan was normal and showed no signs of COVID-19 consolidation, he was given antibiotics and an antipyretic and sent home with strict home isolation instructions. The same patient presented to the Emergency Department for the second time. His symptoms were much worse this time. He had severe shortness of breath, an exacerbated cough, and, most importantly, acute tiredness and exhaustion, as evidenced by his overall appearance. The patient was obviously quite sick, with tachycardia and tachypnea. He required immediate oxygen support because his oxygen saturation levels were only 85%. His neck veins were also significantly congested, and he exhibited an elevated JVP. He exhibited distant heart sounds and bibasilar crackles on chest auscultation. The liver’s left lobe was palpable. However, there was no evidence of ascites or fluid retention elsewhere in the body. He had sinus tachycardia, according to his ECG results. On the ECG, there was obvious ST-segment elevation, which persisted despite the diagnosis of myocardial ischemia. The previous chest X-ray, which was initially normal, revealed cardiomegaly. The data supported the conclusion that the heart played an important role in the equation. This was eventually shown to be a classic case of acute fulminant myocarditis caused by COVID-19. The diagnosis took some time, but because to the patient’s prompt arrival at the Emergency Department, he was admitted, assessed, and treated before any other issues arose. Although patients with pre-existing or a predisposition to developing heart conditions are more inclined towards such outcomes, it can affect almost anyone owing to the complicated nature of the virus itself. Therefore, this case study aims to reflect on all of the possible aspects of this case to make it easier for others to understand and diagnose such cases conveniently. This case report deals with the presenting features as well as the possible treatment options that could be given to such patients who develop fulminant myocarditis as a possible consequence of COVID-19 infection.